A Mobility-Supported Routing Mechanism in Industrial IoT Networks - Jian Cao; Xingwei Wang; Min Huang; Xinhao Zhou (IEEE Access, 2019)
Nowadays, the Industrial Internet of Things (IIoT) has emerged as a promising paradigm for the future network, which intends to connect all kinds of objects, including smart home equipment and intelligent drive devices. Despite the fact that IIoT routing has already attracted a lot of attention from both academia and industry, current researches on IIoT routing cannot effectively solve the mobility problem in a self-adaptive and self-organized manner, because the number of IIoT devices connected is extremely large, and mobility is a very important feature of these IIoT devices. In this paper, a novel routing mechanism based on probability calculation and segment routing is proposed to solve the mobility and scalability problem in IIoT routing. On the one hand, probability calculation can address the extremely unbalanced load condition caused by mobility by forwarding packets to different routings with a certain probability. On the other hand, segment routing enables scalability and flexibility for packet forwarding, and it can also be used to bypass the over-loaded links, thus to achieve load balance. Finally, the simulation results indicate that the proposed mechanism not only solves the mobility problem effectively but also achieves a better performance in many aspects.